Chalmers A. Johnson, Peasant Nationalism and Communist Power: The Emergence of Revolutionary China 1937-1945. Stanford University Press, Stanford, California, 3a. ed., XII + 256 pp. - Thiago Cintra, José (Estudios de Asia y África, 2006)
-